A Genetic Association Study of MTHFR C677T Polymorphism with Risk of Metabolic Syndrome: A Systematic Review and Meta-Analysis - Azizi, Soheil; Shamshirian, Amir; Alizadeh-Navaei, Reza; Jafarpour, Hamed; Asemi, Zatollah; Tamtaji, Omid Reza; Vaziri, Mohammad Sadegh; Homayounfar, Reza; Rezaei Shahmirzadi, Arash; Alipoor, Reza (Galen Medical Journal, 2019)
Methylenetetrahydrofolate reductase (MTHFR) is an enzyme that plays a crucial role as a methyl-group donor in demethylation of homocysteine. The aim of this systematic review and meta-analysis was to study the relationship between MTHFR gene polymorphism and metabolic syndrome (MS). We used search engines and databases such as Science Direct, Google Scholar, Embase, Cochrane Library, and PubMed to identify eligible studies up to 2018. The articles were studied based on keywords including MTHFR, mutation, variant, and polymorphism in combination with MS. Data was analyzed using Comprehensive Meta-Analysis version 2.2.064 software. After extracting the data from seven articles, the total number of subjects was 1280 in the patient group and 1374 in the control group. The odds ratio was estimated to be 1.078 for the allele model of T vs. C (95% confidence interval [CI]: 1.626-0.715), 1.157 for the allele model of CC vs. CT (95% CI: 0.829-1.615), 1.020 for the allele model of CT + TT vs. CC (95% CI: 1.611-0.646) and 0.799 for the allele model of TT vs. CC + CT (95% CI: 1.185-0.539). As well, the results showed no statistically significant correlation between polymorphism genotypes of the MTHFR gene and MS (P<0.05). In general, this study showed that the presence of C677T polymorphism in the MTHFR gene has no effect on the incidence of MS. [GMJ.2019;8:e1472]